Uji Aktivitas Antibakteri Ekstrak Etanol Bunga Telang (Clitoria ternatea L.) Terhadap Bakteri Staphylococcus epidermidis - Fernanda Desmak Pertiwi; Firman Rezaldi; Ranny Puspitasari (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Telang flower (Clitoria ternatea L.) is a plant that has antibacterial properties. The chemical content contained in it which is antibacterial is flavonoids, alkaloids, tannins, saponins and terpenoids. Staphylococcus epdiermidis is one of the bacteria that causes various infections including mild skin infections accompanied by abscess formation. This study aims to test the activity of the telang flower by maceration using 70% ethanol as a solvent. For antibacterial testing with the disk diffusion method. Extracts are made in various concentrations of 10%, 15%, 20%. The positive control used was Chloramphenicol. The results of this study were the average inhibition zone of the telang flower extract against Staphylococcus epidermidis bacteria was 2.31 mm at a concentration of 10%, 3.05 mm at a concentration of 15%, and 6.2 mm at a concentration of 20%. These results indicate that the telang flower extract has antibacterial activity against Staphylococcus epidermidis bacteria, although the inhibition produced is not strong. At a concentration of 20% telang flower extract had the greatest inhibition on the growth of Staphylococcus epidermidis bacteria than the concentrations of 10% and 15%.